Regulation of the somatotropic axis by MYC-mediated miRNA repression - Petrashen, Anna P.; Verdesca, Andrew D.; Kreiling, Jill A.; Sedivy, John M. (Frontiers in Cell and Developmental Biology, 2023)
The transcription factor MYC is overexpressed in many human cancers and has a significant causal role in tumor incidence and progression. In contrast, Myc +/-heterozygous mice, which have decreased MYC expression, exhibit a 10-20% increase in lifespan, decreased incidence or progression of several age-related diseases including cardiac fibrosis, immunosenescence and osteoporosis, as well as a healthier lipid metabolism with age. Myc heterozygous mice also show decreased mTOR and IGF1 signaling, two pathways whose reduced activity is associated with longevity in diverse species. mTOR and IGF1 integrate nutrient availability to promote cellular growth and division, in part through modulating MYC levels. Given MYC's downstream role in these pathways, the downregulation of mTOR and IGF1 signaling in Myc heterozygotes suggests the presence of feedback loops within this regulatory network. We show here that downregulation of Myc leads to upregulation of miRNAs that target the Igf1transcript, thereby inhibiting its translation and leading to decreased IGF1 protein levels. Through Argonaute (AGO)-CLIP-sequencing we find enrichment of AGO binding in the Igf1 transcript at the target sites of let-7, miR-122, and miR-29 in female, but not male Myc heterozygotes. Upregulation of the liver-specific miR-122 in primary hepatocytes in culture and in vivo in mice resulted in significant downregulation of IGF1 protein, but not mRNA. Reduced levels of IGF1 increased GH production in the pituitary through a well-documented negative-feedback relationship. In line with this, we found that IGF1 levels in bone (where miR-122 is not expressed) were unchanged, consistent with the decreased incidence of osteoporosis in female Myc heterozygotes, despite decreased circulating IGF1.